2023
DOI: 10.1097/nmd.0000000000001634
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style and Self-Experience

Abstract: The present study aimed to examine the cross-sectional association between attachment style and self-reported disturbed self-awareness (disturbed sense of mineness of experiences) and depersonalization (disturbed sense of first-person perspective) in patients with psychotic disorders, unaffected siblings, and healthy controls. Data pertain to a subsample of the GROUP (Genetic Risk and Outcome of Psychosis) study. We found positive associations between anxious attachment and disturbed self-awareness and deperso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Three of four studies found no association with anxious (preoccupied) attachment (McGonagle, 2017; Pearce et al., 2017; Williams, 2017), and one found a small positive association (Sitko, 2015). Using a different measure, one study found large positive associations between anxious attachment and both disturbed self‐awareness and depersonalisation (de With et al., 2023). Four studies found no association between avoidant (dismissive) attachment and dissociation (McGonagle, 2017; Pearce et al., 2017; Sitko, 2015; Williams, 2017), one found a trend (de With et al., 2023) and one a small positive association (Degnan, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three of four studies found no association with anxious (preoccupied) attachment (McGonagle, 2017; Pearce et al., 2017; Williams, 2017), and one found a small positive association (Sitko, 2015). Using a different measure, one study found large positive associations between anxious attachment and both disturbed self‐awareness and depersonalisation (de With et al., 2023). Four studies found no association between avoidant (dismissive) attachment and dissociation (McGonagle, 2017; Pearce et al., 2017; Sitko, 2015; Williams, 2017), one found a trend (de With et al., 2023) and one a small positive association (Degnan, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Using a different measure, one study found large positive associations between anxious attachment and both disturbed self‐awareness and depersonalisation (de With et al., 2023). Four studies found no association between avoidant (dismissive) attachment and dissociation (McGonagle, 2017; Pearce et al., 2017; Sitko, 2015; Williams, 2017), one found a trend (de With et al., 2023) and one a small positive association (Degnan, 2020). Austin (2011) did not report these correlations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations